ANALISIS KESIAPAN PENANGANAN MAN OVERBOARD (MOB) DI KM. PANTOKRATOR - Arni Amriani; Oktavera Sulistiana; Nur Indah Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the conformity of procedures and the readiness of safety equipment in handling Man Overboard (MOB) incidents on board KM. Pantokrator. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation study of the ship's Safety Management System (SMS). The results show that the level of conformity in the implementation of MOB procedures reaches 84.6%, where out of 13 procedural steps, 11 were implemented and 2 were not carried out. Several discrepancies were found, particularly in aspects of communication, compliance with procedures, and reporting documentation. From the perspective of safety equipment readiness, the findings indicate that all equipment meets availability standards in accordance with SOLAS requirements, but is not yet optimal in terms of operational readiness. This is evidenced by the ineffective use of the rescue boat, which experienced delays in operation due to the engine condition being rarely used. As a result, the evacuation process was carried out alternatively by the crew using manual methods. Safety equipment such as life jackets and lifebuoys functioned properly, while other equipment was not utilized due to situational considerations. Based on the findings, it can be concluded that although the safety system and equipment are available in accordance with standards, improvements are needed in the areas of equipment maintenance, communication optimization, and reporting accuracy to enhance the effectiveness of emergency handling on board